Pars pro toto or Not? Fragmentation and Identity in the Early Modern Votive Culture - Ulcar, Milena (Acta historiae medicinae, stomatologiae, pharmaciae, medicinae veterinariae, 2025)
Thousands of silver votive plates in the Church of Our Lady of the Reef treasure memory on various types of traumatic events such as illness, slavery, or natural disasters. The aim of this paper is to systemize the ways in which identities of the holy persons and suffering humans were represented, though reexamination of subject-object relatedness in the early modern period.